Genotypic characterization of rpoB, katG and inhA gene of multi drug tuberculosis isolates from extra pulmonary tuberculosis - Anand Kumar Maurya (Biomedical and Biotechnology Research Journal, 2017)
Background: Multidrug-resistant tuberculosis (MDR-TB) has appeared public health concern worldwide. Circulating of drug resistance strains is rising problem in MDR-TB among extra pulmonary TB (EPTB) cases. The objective of this study was to the genotypic characterization of MDR-TB isolates from EPTB and correlate with a phenotypic MDR-TB pattern in this region. Methods: This was study conducted prospectively manner. One hundred and sixty-four M. tuberculosis complex isolates were processed for first-line phenotypic drug susceptibility testing to rifampicin, isoniazid (INH), streptomycin, and ethambutol. Phenotypic confirmed MDR-TB strains were further characterized by gene sequencing for genotypic analysis of rpoB, katG, and inhA. Results: Among 164 MTBC strains, 39.1% of strains were resistant to first-line antitubercular drugs, and 13.4% were MDR-TB along with EPTB cases. In one strain, katG and inhA gene were absent in sequencing analysis. S531 L (61.9%) and S315T (71.4%) mutations were the most predominant mutation in MDR-TB isolates among EPTB cases. Conclusion: Molecular drug resistance testing allows to improved diagnosis, reduces the risk of additional resistance and effective treatment of drug resistance TB. Molecular DST testing can help in the detection for MDR-TB which helps in the prompt initiation of effective antitubercular therapy.